Perilaku Judi Di Desa Boncah Mahang Kecamatan Mandau Kabupaten Bengkalis - Lia Chesia; Hesti Asriwandari (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
Research was conducted in Boncah Mahang Village, Mandau District, Bengkalis Regency. This research aims to determine fish gambling activities and interactions between players and spectators in gambling and fish. The activities and interactions that occur involve players and spectators who have relationships within the group. This research uses descriptive qualitative research methods. With a total of 6 subjects, they are also involved in carrying out activities and interactions in fish gambling, then they are native people of the village who carry out gambling activities and they are able to define and explain a process of how interactions and gambling activities run based on existing facts. To collect data using observation techniques, in-depth interviews and also documentation. The theories used are labeling theory and also Edwin Sutherland's theory of social deviance. Research in the field found that activities and interactions occur due to internal and external encouragement. What is meant by internal encouragement is encouragement that comes from within oneself and external is encouragement that comes from outside oneself, for example being able to carry out gambling activities or gambling interactions due to temporary access to friends. Internal encouragement is encouragement that originates from oneself, for example one's desire to experience entertainment, curiosity, eliminate feelings of loneliness and the urge from within oneself to get the main prize even though it is not certain. The gambling table, which is precisely located in Boncah Mahang Village, is currently still active, therefore gambling activities and interactions between players and spectators are still ongoing and active today and are still ongoing.